2017
DOI: 10.1089/ten.teb.2016.0280
|View full text |Cite
|
Sign up to set email alerts
|

Design and Use of Chimeric Proteins Containing a Collagen-Binding Domain for Wound Healing and Bone Regeneration

Abstract: Collagen-based biomaterials are widely used in the field of tissue engineering; they can be loaded with biomolecules such as growth factors (GFs) to modulate the biological response of the host and thus improve its potential for regeneration. Recombinant chimeric GFs fused to a collagen-binding domain (CBD) have been reported to improve their bioavailability and the host response, especially when combined with an appropriate collagen-based biomaterial. This review first provides an extensive description of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 196 publications
1
40
0
Order By: Relevance
“…Further, taking cue from a recent review, we plan to design collagen binding osteoinductive peptides for wound healing and bone tissue regeneration. [42] Taken together, the 3D hybrid nanofiber aerogels incorporated with osteoinductive peptides is a promising direction for the development of synthetic bone grafts. Another approach for promoting bone tissue ingrowth into the defect area is through the fabrication of porous scaffolds with radially aligned pores by directional freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Further, taking cue from a recent review, we plan to design collagen binding osteoinductive peptides for wound healing and bone tissue regeneration. [42] Taken together, the 3D hybrid nanofiber aerogels incorporated with osteoinductive peptides is a promising direction for the development of synthetic bone grafts. Another approach for promoting bone tissue ingrowth into the defect area is through the fabrication of porous scaffolds with radially aligned pores by directional freezing.…”
Section: Discussionmentioning
confidence: 99%
“…When a blood vessel is injured, collagen beneath the endothelial cells is exposed to proteins in the blood, and VWF binding to collagen initiates the thrombosis cascade (26). The VWF A domain has the highest affinity for collagen among reported non-bacterial origin proteins/peptides (27). Particularly within the A domain, the A3 domain of VWF has been reported as a collagen-binding domain (CBD, using this abbreviation to refer specifically to the VWF A3 collagen-binding domain) (28).…”
Section: Introductionmentioning
confidence: 99%
“…We then further detected the expression of BDNF in TBI lesions and found that the expression of BDNF in TBI lesions was higher in TBI + CBD‐BDNF group than that in TBI group and TBI + BDNF group. Actually, collagen‐derived biomaterials have been widely developed for tissue engineering and regenerative medicine purposes for their excellent biocompatibility and biodegradability, along with high safety and weak antigenicity . Therefore, we suppose that the superior effects of CBD‐BDNF come from its better ability to cross the blood–brain barrier, which makes it promising in clinical application.…”
Section: Discussionmentioning
confidence: 99%